-3(x-4)-(2x-7)=

Simple and best practice solution for -3(x-4)-(2x-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-4)-(2x-7)= equation:


Simplifying
-3(x + -4) + -1(2x + -7) = 0

Reorder the terms:
-3(-4 + x) + -1(2x + -7) = 0
(-4 * -3 + x * -3) + -1(2x + -7) = 0
(12 + -3x) + -1(2x + -7) = 0

Reorder the terms:
12 + -3x + -1(-7 + 2x) = 0
12 + -3x + (-7 * -1 + 2x * -1) = 0
12 + -3x + (7 + -2x) = 0

Reorder the terms:
12 + 7 + -3x + -2x = 0

Combine like terms: 12 + 7 = 19
19 + -3x + -2x = 0

Combine like terms: -3x + -2x = -5x
19 + -5x = 0

Solving
19 + -5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-19' to each side of the equation.
19 + -19 + -5x = 0 + -19

Combine like terms: 19 + -19 = 0
0 + -5x = 0 + -19
-5x = 0 + -19

Combine like terms: 0 + -19 = -19
-5x = -19

Divide each side by '-5'.
x = 3.8

Simplifying
x = 3.8

See similar equations:

| 8y-3=4y+5 | | 8x+8=6x+34 | | 4(x+3)=2x-2 | | 3(4x-1)=39 | | 4(3x+8)= | | 5x-15=100 | | c^2=18-3c | | -2x^2-3x-1=0 | | 2v^2+11v+5v= | | y(y+2)+(t+2)-9=0 | | 5c-7+17= | | -(3z-1)-2(z+9)=7(z+1) | | 22y-7x+3-2y+x= | | 2x^2+x=45 | | 6x-2=18x+2 | | 4x+20=7x+5 | | 3x-2x+3=0 | | x+(70000*.09)=70000 | | (v-1.4)(v+1.4)= | | 25v^2-49= | | 9(x+11)+5(13x)=0 | | (-1-2m)(5-3m)= | | x+3y=776 | | 7y+2=51 | | 12x^2-16x-3=0 | | 5a^2+24a-5= | | x+y=250 | | 2x-9=-8 | | 2*-9=-8 | | 3p^2=-4p-1 | | 3x^2=4x+11 | | 2x+5y=1252x-y-10 |

Equations solver categories